Oviposition Decisions by Red Flour Beetle [Tribolium castaneum] - Curtright, Taylor; Campbell, James (My University, 2018)
The red flour beetle [Tribolium castaneum] and the confused flour beetle [Tribolium confusum] are very important flour pest. We tested if the red flour beetle can discriminate between flour infested by the same species or congeneric species and lay different number of eggs. Results of the choice tests were inconclusive, because oviposition across all the treatments was very low. Future research will be needed manipulating the female age and the length of time in the arenas to be able to address the proposed question. With this future research, it will hopefully help us better understand how these beetles exploit flour patches and improve management in flour mills.
Keywords: Fall 2018